Cardiovascular health among the Czech population at the beginning of the 21st century: a 12-year follow-up study - Lustigova, Michala; Dzúrová, Dagmar; Pikhart, Hynek; Kubinova, Ruzena; Bobak, Martin (Journal of epidemiology and community health, 2018)
BACKGROUND: In the late 1980s, Czechia was among the countries which had the highest cardiovascular mortality in the world. In spite of enormous improvements since that time, there are still large opportunities in further improving cardiovascular health. METHODS: Based on the Czech Health, Alcohol and Psychosocial Factors in Eastern Europe sample (n=8449 at baseline, 12 years of follow-up, 494 cardiovascular disease (CVD) deaths up to 2015-events), the impact of selected covariates such as education, smoking habits, high blood pressure, blood cholesterol level, diabetes, obesity, physical activity and binge drinking and their multifactorial effects on cardiovascular mortality was evaluated by Cox regression. In addition, population attributable fractions (PAFs) were used to quantify the impact of these factors on CVD mortality in the population. RESULTS: Education was found as the strongest determinant of CVD mortality (primary vs university, HR 2.77, P<0.001; PAF=50.5%). CVD risk was two times higher for persons with diabetes compared with those without (HR 2.02, P<0.001, PAF=23.2%). Furthermore, significant factors found were smoking (smoker vs non-smoker, HR 1.91, P<0.001; PAF=26.5%), high blood pressure (HR 1.73, P<0.001; PAF=35.3%) and physical inactivity (none vs sufficient, HR 1.60, P<0.001; PAF=22.9%). Conversely, the effect of obesity was low (HR 1.29, P value =0.020), and binge drinking and high blood cholesterol level were not significant at all. CONCLUSIONS: Education had the largest impact on cardiovascular mortality among the Czech population. More than 50% of CVD death would be prevented if the whole population had the same risk values as the highest educated population. Reducing disparities in health related to education should benefit from attention to cardiovascular health literacy.
Keywords: kouření; Cholesterol; Smoking; komorbidita; následné studie; lidé; Middle Aged; Adult; hypertenze; kardiovaskulární nemoci; cholesterol; diabetes mellitus; Female; Humans; Educational Status; Follow-Up Studies; Diabetes Mellitus; Comorbidity; Socioeconomic Factors; stupeň vzdělání; Česká republika; lidé středního věku; mužské pohlaví; Cardiovascular Diseases; Hypertension; Binge Drinking; socioekonomické faktory; ženské pohlaví; Czech Republic; Alcohol Drinking; Male; Aged; nárazové pití alkoholu; dospělí; pití alkoholu; senioři